Pattern of Immunoglobulin Synthesis and Assembly in a Human-Mouse Somatic Cell Hybrid Clone - Schwaber, Jerrold (1974)
Fusion of human peripheral blood lymphocytes, not forming detectable immunoglobulins, with mouse myeloma cells (TEPC-15), secreting mouse immunoglobulin A with known antibody activity, yielded a somatic cell hybrid clone that secreted both human and mouse immunoglobulins. Analysis by sodium dodecyl sulfate-polyacrylamide gel electrophoresis indicated that human gamma, alpha, and light chains, as well as mouse alpha and light chains, were formed by the hybrid cells. To determine whether individual antibody molecules with both human and mouse components were secreted, medium from the hybrid cells was precipitated first with antibody against mouse immunoglobulin produced in rabbit, reduced, and alkylated, and then reprecipitated with antibody against human immunoglobulin produced in rabbit. Human gamma, alpha, and light chains were detected after electrophoresis of the immunoprecipitates on sodium dodecyl sulfate-polyacrylamide gels, indicating that antibody molecules containing both human and mouse components were secreted by the hybrid cells. These data indicate that this somatic cell hybrid clone synthesized human gamma and alpha heavy chains and human light chains, as well as mouse alpha heavy chains and mouse light chains. Some of these immunoglobulin components were assembled as hybrid antibody molecules.